2020
DOI: 10.1111/ele.13624
|View full text |Cite
|
Sign up to set email alerts
|

Selection against immigrants in wild seabird populations

Abstract: Immigration is a major demographic parameter shaping population dynamics and is an important driver of eco-evolutionary patterns, but the fitness consequences for individuals following their settlement to a new population (immigrants) remain poorly tested in wild animal populations, particularly among long-lived species. Here we show that immigrants have a lower fitness than residents in three wild seabird populations (wandering albatross Diomedea exulans, southern fulmar Fulmarus glacialoides, snow petrel Pag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Bias in demographic parameters were higher in the long-lived species characterized by a higher proportion of adults and thus of immigrants, than in the short-lived species characterized by a higher proportion of juveniles. Moreover, the bias in parameter estimates is expected to change if immigrants have different survival and reproductive success than residents (Grist et al 2017;Rolandsen et al 2017;Barbraud and Delord 2021).…”
Section: Generality and Limits Of Our Resultsmentioning
confidence: 99%
“…Bias in demographic parameters were higher in the long-lived species characterized by a higher proportion of adults and thus of immigrants, than in the short-lived species characterized by a higher proportion of juveniles. Moreover, the bias in parameter estimates is expected to change if immigrants have different survival and reproductive success than residents (Grist et al 2017;Rolandsen et al 2017;Barbraud and Delord 2021).…”
Section: Generality and Limits Of Our Resultsmentioning
confidence: 99%
“…If some local habitats are more suited than others (i.e., with higher quality), then some valleys will show a higher proportion of gulls recaptured with natal philopatry returning every year (philopatry benefits) [38,39]. Conversely, dispersers (i.e., gulls coming from any other nesting area) should be captured less frequently (selection against immigrants) [42]. For instance, a recent study found evidence of selection against immigrants, which were found to have a lower fitness than residents in wild seabird populations of three long-lived Procellariiformes species (Wandering Albatross Diomedea exulans, Southern Fulmar Fulmarus glacialoides, and Snow Petrel Pagodroma nivea) [42].…”
Section: Philopatry and Dispersal Behaviormentioning
confidence: 99%
“…Conversely, dispersers (i.e., gulls coming from any other nesting area) should be captured less frequently (selection against immigrants) [42]. For instance, a recent study found evidence of selection against immigrants, which were found to have a lower fitness than residents in wild seabird populations of three long-lived Procellariiformes species (Wandering Albatross Diomedea exulans, Southern Fulmar Fulmarus glacialoides, and Snow Petrel Pagodroma nivea) [42]. Other interactions may include the deterring by successive occupation of other birds arriving in large numbers or predation (Figure S2), in addition to differences in egg sizes influenced by nest densities, habitat, and nest-site selection, as have been the cases for the Herring Gull (Larus argentatus) and the Common Gull (L. canus) [101,102].…”
Section: Philopatry and Dispersal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…During both transience and settlement, dispersers are also likely to suffer missed feeding opportunities [75] and greater stress [27], likely generating substantial life-history costs (e.g. [76]). In agreement, Johnson et al [77] found that mortality risk increased with dispersal distance in juvenile American martens (Martes americana) so that individuals in poor condition settled closer to their natal range.…”
Section: (C) Individual Quality and The Cost Of Dispersalmentioning
confidence: 99%